Tindak Kesantunan Direktif Dalam Pelayanan Di Bidang Kesehatan Di Lingkungan Puskesmas Berlatar Belakang Budaya Jawa Dan Implikasinya Sebagai Bahan Ajar Bahasa Indonesia Di SMA/SMK - Lestari, Anjar, Prof. Dr. Harun Joko Prayitno, M.Hum (2017)
This research includes three objectives, (1) describing the form and intent of directive in health service in the community health center with the background of Javanese culture (2) describing the strategy of directive acts in health service in the health center environment of Javanese culture, and (3) describes the implications of directive in health service into Indonesian language learning in SMA / K. Method of data collection that refer to the method with tapping technique, SLBC techniques, recording techniques and record. Data analysis techniques include methods of unified referential, translational and pragmatic frontier. The results of this qualitative research in the form of twenty forms of speech acts and two positive politeness strategy (8 actions realization) and negative politeness strategies (9 act of realization). This study can also be implied as Indonesian teaching materials in class X SMA 2nd semester in accordance with the decree. Writing and KD. 12.2.